Reseña de: Mari Carmen SERRA PUCHE, José Francisco MEJÍA FLORES y Carlos SOLA AYAPE (eds.), De la posrevolución mexicana al exilio republicano español, México, Fondo de Cultura Económica Cátedra del Exilio, 2011 - Herrera González, Patricia (Historia del Presente, 2013)
-